The different uses of the pronoun ‘we’ by EFL teachers in classroom interaction - Muthi'ah Muthi'ah; Syamsul Arif Galib; Annisa Shofa Tsuraya; Multazam Abubakar; Nur Aliyah Nur; Muhammad Syahruddin Nawir (Universitas Syiah Kuala, 2022)
The pronoun ‘we’ is understood only to refer to the first-person plural. In fact, the pronoun ‘we’ can also refer to other references. The primary purpose of this study is to examine the different uses of the pronoun ‘we’ by EFL teachers in classroom interaction. This study employed a qualitative approach by using three instruments: observation, audio-recorder, and interview in collecting the data. The subjects of this research are two English teachers and the second-grade students at a vocational high school in Makassar. The data were analyzed by formulating Miles et al.’s method of analysis. The result of this study shows that, in classroom interaction, the pronoun ‘we’ can refer to six distinct references: (1) ‘we’ that refers to speaker and more than one addressee, (2) ‘we’ that refers to speaker and more than one-third party, (3) ‘we’ that refers to speaker and indefinite group, (4) ‘we’ that indicates ‘you’, (5) ‘we’ that indicates ‘I’, and (6) ‘we’ that indicates “they”. From the interviews, the researchers found that both teachers have different reasons for using the pronoun ‘we’ in classroom interaction. The first teacher intends to use the pronoun to help him create an enjoyable learning environment and establish better relationships with the students. In contrast, the other teacher uses the pronoun ‘we’ to show politeness to the students. Despite the differences, they both seem to have the same intention of creating a positive learning environment.